2016
DOI: 10.1016/j.jcte.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral sensory neuropathy in type 2 diabetes patients: A case control study in Accra, Ghana

Abstract: HighlightsPSN was assessed by symptoms, examination and quantitative assessment.High burden of PSN in diabetes patients in Ghana.The major determinants of PSN using different assessment methods were reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 23 publications
5
15
0
1
Order By: Relevance
“…Finally, the present study found a significant association between smoking habit and DPN. Other studies have also found a similar association [ 32 , 43 ]. The association between smoking and DPN can be explained by the fact that smoking causes neuropathy via neuronal ischemia from endothelial damage, increased inflammation, oxidative stress, interference with glucose metabolism, and from direct toxic effects on the neurons [ 48 ].…”
Section: Discussionsupporting
confidence: 73%
“…Finally, the present study found a significant association between smoking habit and DPN. Other studies have also found a similar association [ 32 , 43 ]. The association between smoking and DPN can be explained by the fact that smoking causes neuropathy via neuronal ischemia from endothelial damage, increased inflammation, oxidative stress, interference with glucose metabolism, and from direct toxic effects on the neurons [ 48 ].…”
Section: Discussionsupporting
confidence: 73%
“…Diabetes is now common in sub-Saharan African population and associated with macrovascular and microvascular complications [ 1 , 2 ]. Cardiovascular diseases are among the major causes of death in diabetes patients; however, studies have shown that microvascular disease is also associated with excess mortality [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic adult diseases including hypertension, obesity, resulting metabolic syndrome and diabetes are now common [ 1 , 2 ]. Consequently, premature macro- and micro-vascular conditions, including hypertensive heart failure (if not yet much coronary disease), stroke, renal failure, and arterial complications of Type 2 diabetes (T2D) now burden patients and health services [ 3 , 4 ]. Arterial stiffness is a powerful predictor of such future cardiovascular (CV) complications and all-cause mortality in all patient groups studied, even after adjusting for age, blood pressure (BP) or other risk factors [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%